ChemInform Abstract: Applications of Graphene and Its Derivatives as an Adsorbent for Heavy Metal and Dye Removal: A Systematic and Comprehensive Overview. Issue 31 (August 2015) - Yusuf, Mohammed; Elfghi, F. M.; Zaidi, Shabi Abbas; Abdullah, E. C.; Khan, Moonis Ali
Abstract Review: 168 refs.